Down in the valley. - Norton, Edward; Burstyn, Ellen, 1932-; Morse, David, 1953-; Dern, Bruce; Culkin, Rory.; Wood, Evan Rachel, 1987-; Jacobson, David ([United States] : Thinkfilm, Llc, 2005)
Harlan is a cowboy stuck in San Fernando Valley, where he meets a rebellious young girl, Tobe. Their encounter explodes into a passionate romance, but sinister truths are lurking beneath Harlan's charm.
Producer, Sam Nazarian; director, David Jacobson.
Keywords: Drama films